A close monitoring of Variations in Fatty acid profile of Isochrysis galbana under conditions of limited Nutrition - Ganga, Rajani S.; Anandan, R.; Joseph, Aneykutty (Fishery Technology, 2020)
The current study was aimed at investigating the possible deviations in the degree of unsaturation of fatty acid components in the marine microalga Isochrysis galbana, under conditions of low nitrogen as well as low phosphorus concentrations. Standard f/2 medium in filtered and sterilized sea water of salinity 33ppt was used as control/N100. The other treatments used were f/2 medium with 25% nitrogen source (N25) and f/2 medium with 25% phosphorus source (P25). For control cultures, saturated fatty acids (SFAs) accounted for over 70.66% of the total fatty acids, whereas it was only 62.96% in nitrogen limited cultures and 60.17% in phosphorus limited ones. The present study reveals that nutrient stress provided a remarkable elevation in the degree of unsaturation. The value of monounsaturated fatty acids (MUFAs) was maximum for N25 cultures (22.20%) followed by P25 (19.62%) whereas it was 16.81% for control. Among the three treatments, the highest value of polyunsaturated fatty acids (PUFAs) observed in the P25 cultures (20.21%) followed by 14.84% (N25) while it was only 12.52% for control cultures. One way analysis of data brought to light that nutrient stress can influence fatty acid pattern of the microalga significantly (p<0.05). The present observations suggest that low availability of macronutrients such as nitrogen or phosphorus can shift the fatty acid profile from saturated to unsaturated.